Missed opportunities for tetanus vaccination in pregnant women, and factors associated with seropositivity - (:unkn) unknown (W B SAUNDERS CO LTD, 2004)
The aim of this study was to identify the seroprevalance rate of tetanus and to determine missed opportunities for tetanus vaccination. Two hundred and twenty-seven female volunteers who were hospitalized following delivery participated in the study. Blood samples were analyzed using enzyme-linked immunoassay to measure tetanus antibody levels. In addition, a questionnaire was used to investigate the factors associated with vaccination status. Sixty-five percent of the study participants had safe protective levels of antibodies. Factors associated with antibody level were age, level of education and number of doses. Only 25.7% of women who received antenatal care (ANC) had received tetanus vaccinations. Women who received ANC from primary healthcare facilities were more likely to have been vaccinated than those who received ANC from hospitals or private practice (P < 0.05). Factors associated with both tetanus vaccination and immunizations in pregnant women should be further investigated by qualitative and quantitative studies. Knowledge, attitude and practice surveys of mothers and healthcare providers on provision of the tetanus vaccine to pregnant women need to be undertaken urgently. (C) 2004 The Royal Institute of Public Health. Published by Elsevier Ltd. All rights reserved.
Keywords: neonatal tetanus; missed opportunities for vaccination; tetanus seroprevalance; maternal health; IMMUNIZATION; ANTIBODY; TURKEY